Analisis Potensi Longsor pada Ruas Jalan Malalak Km 33 di Kecamatan Malalak, Kabupaten Agam, Provinsi Sumatera Barat - Resty Prasuryani; Rusli HAR; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Based on observations made on Sicincin-Malalak street KM 33 have been found 12th failure point with various conditions and types of failure. In addition, the geometry of the slope, high intensity of the earthquake and rainfall greatly affect to the condition of slope stability. The research was done on rock  slope with many joints, steep geometry, and many rockfalls. From these problem, we need to measure the physical characteristic, compressive strength and rock mass condition in research area using Rock Mass Rating (RMR) classification. Furthermore, the analysis of potential failure in the research area doing using dips to know the type of failure and then analyzed the stability of the slope using the limit equilibrium  method.  The results of rock mass classification with RMR obtained rocks included in Group II which means rock mass in good condition. Analysis using dips in get type of failure is toppling failure with possibly 15,53% with failure stike = N 225 E - N 285 E and dip = 15° - 90°. Furthermore, slope stability analysis was performed using the equilibrium limiting method for toppling failure and obtained FK values of slope is 1,58 which means that the slope is stable but still need protection from rock fall with construction of ditch and wiremesh instalation.Keyword: Failure, limit equilibrium method, toppling, slope stability, RMR